Method of pedagogic instruments design for software engineering [Método de diseño de instrumentos pedagógicos para ingeniería de software] (2016)
Software quality is a critical aspect in the development process of products for several economic sectors (ie. industry, services, agricultural, etc.). CMMI, ISO standards, Personal Software Process (PSP), and Team Software Process (TSP) are examples of approaches for improving software quality. Teaching such approaches is a challenge because of the amount of concepts, practices, and statistics required for their adoption, generating problems related with low motivation and poor performance in students or professionals in training. In the literature several approaches for solving these problems are presented, some of them incorporating active learning strategies like case method, simulation, and gamification. In this paper we propose a method for facilitating the design of teaching strategies based on gamification principles, looking for increasing the student motivation in their learning process. As a way to evaluate the proposed method, a pilot study case for teaching subjects related to software design in the context of PSP is presented. © 2016 AISTI.